PROJECTION AND AXONOMETRY (Academicia Globe: Inderscience Research, 2022)
Article Projection, Creation of Central and Parallel Projections, View, Execution of Views, Orthogonal Projection, Representation of Machine Details, Model, Three Views of a Model, Representation of a Model, Additional and Local Views, exercises for convenient and easier understanding, analysis of drawings to reinforce what we know by repeating what we don't know, gives information about axonometric images and types. The peculiarity of the article is that it covers more than five topics and provides full information about them.